1987
DOI: 10.1073/pnas.84.23.8463
|View full text |Cite
|
Sign up to set email alerts
|

Transfection of mammalian cells with plasmid DNA by scrape loading and sonication loading.

Abstract: Scrape loading and sonication loading are two recently described methods of introducing macromolecules into living cells. We have tested the efficacy of these methods for transfection ofmammalian cells with exogenous DNA, using selection systems based either on resistance to the drug G418

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
150
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(151 citation statements)
references
References 27 publications
0
150
0
Order By: Relevance
“…16 Similarly, lithotripter shock waves, a special form of ultrasound waves with high pressure amplitudes, have been shown to enhance the transfer of ribosome inactivating proteins into malignant cells in vivo. 17 Other in vitro reports indicate that genes can be transferred into mammalian cells 18 and plants 19 by ultrasound cleaning and sterilization equipment. In recent in vitro experiments sinusoidal ultrasound [20][21][22] and lithotripter shock waves were used to mediate plasmid DNA transfer into mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…16 Similarly, lithotripter shock waves, a special form of ultrasound waves with high pressure amplitudes, have been shown to enhance the transfer of ribosome inactivating proteins into malignant cells in vivo. 17 Other in vitro reports indicate that genes can be transferred into mammalian cells 18 and plants 19 by ultrasound cleaning and sterilization equipment. In recent in vitro experiments sinusoidal ultrasound [20][21][22] and lithotripter shock waves were used to mediate plasmid DNA transfer into mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21] Ultrasound treatment has been used to introduce DNA vectors into yeast, plant cells, and mammalian cells in vitro. [19][20][21] In this study, we have demonstrated the application of ultrasound treatment for gene transfer to primary tumors in mice. More than a two-log increase in systemic gene transfer to primary tumor by sonoporation without any effect on gene expression in nontumor tissue demonstrates the usefulness of ultrasound for systemic gene targeting to primary tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-enhanced delivery to cells has been demonstrated in vitro by uptake of extracellular fluid, drugs, and DNA into cells. [17][18][19][20][21] In the present study we describe the combination of an ultrasound method and systemic administration of cationic lipid/DNA complexes that provides for specific enhancement in gene transfer to primary tumors. The enhancement in gene transfer was restricted to sonoporated tumors and no effects were observed in non-sonoporated tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Inset: Observed resistance to anti-BPDE was proportional to the percentage of GST n + cells in the electroporated population. 11. Survival of reverted GST n+ COS cells after exposure to anti-BPDE in a colony-forming assay.…”
Section: Gst M-conferred Resistance To Anti-bpde Inmentioning
confidence: 99%